A high‐selectivity wideband bandpass filter with multiple transmission poles and zeros. Issue 4 (9th February 2021) - Yu, Huiting; Wu, Yongle; Wang, Weimin
Abstract: In this paper, a simple high‐selectivity wideband bandpass filter based on a novel π‐shaped coupled‐line structure is introduced. The presented filter realizes wide bandwidth, excellent passband selectivity and good stopband suppression by using two coupled lines with diagonal open‐circuited ports and three coupled lines with cascaded ports. The design theoretical analysis and the complete equation derivation are provided in detail. Furthermore, a prototype with 3‐dB fractional bandwidth of 50.9% is simulated, fabricated, and measured. The simulated and measured results have a good consistency, which verifies the analytical design principle.